A Critical Study on Credit Cards and Its Future In India: Examining the Impact of Credit Cards on Consumer Behavior in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A “CreditCard‟ is defined as “A plastic card having a magnetic ribbon, issued by a bankor business authorizing the holder to purchase goods or services on credit”.„Users‟ experience‟ involves “all factors of the end-user’s interface with the company,its services and its products… and its capability… to convene the preciserequirements of the client”. It basically points to the users‟ views aboutusing the product or services.  It istherefore prejudiced and concentrates on whether the product / service generatesignificance for them and fulfills their needs. It is subjective, vibrant andchanges with time and conditions.